Relocation of Monuments in Kwelachhi of Lubhu - Shilpakar, Rabina; Shrestha, Sandip (Journal of Science and Engineering, 2026)
Lubhu, a historically important city located in the Lalitpur district, houses numerous monuments from different historical timeline. Lubhu is home to several centuries’ old monuments where some monuments still are intact today though facing many changes due to natural calamities like earthquake while some has undergone changes with the changing urban development factors such as infrastructure expansion especially the road widening projects. Few of such examples are located in the Kwelachhi tole of Lubhu. In 2022, the temples dedicated to Ganesh and a chaitya has been relocated few distance apart to clear the roadways considering the future road expansion in the area. This study focuses on these two temples of the roadside which were shifted to short distances from the original position. The study will focus on the process of relocation of these temples and the issues arouse among the locals. The role of community involvement is important in such conservation programs as they are the users of those monuments in their daily social life. This research will study the engagement of the community in different phases of conservation. The methodologies to conduct this research will be questionnaire surveys, interviews, study of the old photographs, and site inspections. The data will be qualitatively and quantitatively analysed on conservation efforts applied on those structures by the concerned authorities.